MAPS 15504 : uma metodologia de avaliação de processo de software para o ExPSEE naseada no ISO/IEC TR 15504 - Padilha, Ademir Morgenstern (2000)
Orientadores: Jacques Wainer, Itana Maria Souza Gimenez